Analisis Model Newcomb, One-Step Flow, dan Two-Step Flow dalam Proses Kampanye Digital Pilkada 2024 di Sumatera Utara - Mulkan Darajat Silaen; Syukur Kholil (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to analyze the application of three communication models Newcomb, One-Step Flow, and Two-Step Flow  in the 2024 Regional Election digital campaign in North Sumatra. The method used is a qualitative approach with literature review, collecting secondary data from various related literature. Newcomb's model emphasizes the importance of interpersonal relationships in political communication, where potential leaders and voters must have the same attitude to increase the effectiveness of campaign messages. Through social media, these interpersonal relationships are built through two-way interactions that strengthen voter trust and loyalty. The One-Step Flow model, on the other hand, focuses on delivering a direct message from a candidate to an audience without traditional intermediaries. The use of platforms such as Instagram and Twitter allows potential leaders to convey messages quickly and responsively, especially to young voters who are more active in digital media. However, this model faces challenges in the dissemination of misinformation or manipulation of public opinion. The Two-Step Flow model underlines the important role of opinion leaders, such as influencers and community leaders, in filtering and disseminating campaign messages. They act as intermediaries who are able to bridge communication between prospective leaders and voters, provide more personalized interpretations, and increase voter participation. The results show that the combination of these three communication models forms a more holistic and adaptive digital campaign strategy. The proper use of social media, strong interpersonal interaction, and the involvement of opinion leaders can increase the effectiveness of campaigns, political participation, and a positive image of prospective leaders. This strategy is relevant in facing the diverse demographic and cultural challenges in North Sumatra, as well as helping to build the legitimacy of the candidates in the eyes of the public.